Environmental Effects of Sulphate on Conventional Concrete Based on Portland Composite Cement - Yuyun Tajunnisa; Nur Achmad Husin; Sigit Darmawan; M. Faishal Darmawan; Suwandi Suwandi; Mitsuhiro Shigeishi (IPTEK The Journal of Engineering, 2023)
Concrete performances have weaknesses; one of those weaknesses is that it is significantly affected when put in a high sulfate and chloride environment. This study aims to investigate sulfate's effect on PCC concrete's performance. In this research, PCC concrete was immersed in water for 28 days and conducted after the casting. After being soaked in water, three immersed specimens were removed and immersed in magnesium sulfate solution for 24 days and 84 days, whereas three others were removed and immersed in natrium sulfate solution for 24 days and 84 days. The observation showed that PCC concrete's average compressive strength test with water immersion was 42.17 Mpa. It meets the SNI 2847:2019 Indonesian standard for sulfate classification S1. The specimens decreased to 30.74 Mpa after being soaked in the magnesium sulfate solution for 28 days and again reduced to 25.39 Mpa at 84 days. The average compressive strength of specimens bathed in the sodium sulfate solution for 28 days was 32.19 Mpa. It decreased to 28.03 Mpa at the age of 84 days. The results of this study show that the compressive strength of PCC concrete soaked in sodium sulfate meets the SNI 2847:2019 standard for sulfate classification S1, which is more than 28 Mpa. The compressive strength of PCC concrete immersed in magnesium sulfate for 1 month (28 days) is more than 28 MPa. It meets the standard as well. Yet, the compressive strength of PCC concrete soaked in magnesium sulfate for 3 months (84 days) does not meet the standard.